2017
DOI: 10.1175/jcli-d-16-0152.1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical–Extratropical Interactions Associated with East Asian Cold Air Outbreaks. Part I: Interannual Variability

Abstract: Interannual variability of winter-mean East Asian cold air outbreaks (CAOs) and its relationship with the tropical climate system during 56 boreal winters (DJF) are investigated. The magnitude of CAO is quantified as winter-mean equatorward cold airmass (CAM) flux below 280-K potential temperature across the 45°N latitude. EOF analysis shows that the interannual variation of East Asian CAOs is attributed mainly to the contributions from western and eastern CAOs. In particular, the western and eastern CAOs tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…In the central North Pacific, equatorward flux anomalies appear (Figures 2b and 2d). This signature was observed in a previous study that showed that El Niño enhances the eastern part of the East Asian stream (Abdillah et al, 2017). The anomalous equatorward flow extends to midlatitudes and ultimately represents the increase in zonal-mean cold air outflows at the critical latitude of two-box model (Table 1).…”
Section: Geographical Patterns Of Pcam Anomaliessupporting
confidence: 78%
See 4 more Smart Citations
“…In the central North Pacific, equatorward flux anomalies appear (Figures 2b and 2d). This signature was observed in a previous study that showed that El Niño enhances the eastern part of the East Asian stream (Abdillah et al, 2017). The anomalous equatorward flow extends to midlatitudes and ultimately represents the increase in zonal-mean cold air outflows at the critical latitude of two-box model (Table 1).…”
Section: Geographical Patterns Of Pcam Anomaliessupporting
confidence: 78%
“…In the east of the cyclonic anomaly center, poleward flux anomalies emerge that span from off the coast of western North America to inland North America. In the east of the Rocky Mountains, the poleward flux anomalies are situated over the climatological North American stream and indicates the decrease in equatorward advection of the PCAM which eventually causes a reduction in the PCAM amount (Abdillah et al, ; Kanno et al, ). In Alaska, westward flux anomalies prevail and also cause a significant PCAM reduction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations